A comparative study of tympanoplasty with or without mastoidectomy in tubotympanic type of chronic suppurative otitis media - Nambiar, Rachna Vijayan; Priyadarshini, G.; Tiwari, Aishwarya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: CSOM is one of the most common ear diseases in developing countries. Lack of an aerating mastoidectomy at the time of the initial tympanoplasty may be a significant source of failure in patients with chronic non-cholesteatomatous otitis media so cortical mastoidectomy along with tympanoplasty has for long been considered the surgical procedure of choice. The purpose of our study is to ascertain the effectiveness of tympanoplasty with or without cortical mastoidectomy. Methods: Our study was carried out in the Department of Otorhinolaryngology, Aarupadai Veedu Medical College, Pondicherry. It included 50 patients of CSOM tubotympanic type of age between 15 years to 45 years and of either sex who were diagnosed and treated in E.N.T Department during the study period October 2016 to August 2018. Out of 50 patients who underwent surgery in 25 cases tympanoplasty with mastoidectomy was done and tympanoplasty without mastoidectomy was performed in 25 cases. Results: Commonest age group was 15-19 years. Male to female ratio was 1.6:1. In x-ray bilateral mastoids Schuller’s view, 24 patients (48%) had sclerotic mastoids and 26 patients (52%) showed pneumatic mastoids. Clinical improvement, graft uptake and postoperative hearing improvement was similar in both the groups. Conclusions: Most common age group of presentation with CSOM tubotympanic type is 15-25 years. CSOM tubotympanic type appears to be more common in males. Hearing improvement following tympanoplasty alone and tympanoplasty with mastoidectomy were comparable in both the groups. Mastoidectomy with tympanoplasty does not give additional benefit in terms of hearing improvement.